Biomodeling and 3D printing: A novel radiology subspecialty - Silvina Zabala Travers (Elsevier, 2021)
3D biomodels are a new kind of medical image that enables easier interpretation of medical imaging findings, virtual surgical planning and 3D printing of anatomical biomodels and personalized surgical tools. New applications emerge every week in all surgical specialties for diagnostic, treatment and educational purposes. High performance software is available for biomodeling but it still requires human supervision to ensure biomodel fidelity with patient anatomy. Radiology technologists, bioengineers or other health care providers may have sufficient training to provide accurate segmentation in most cases. However, radiologists should be involved to add their expertise in medicine and medical imaging since there is a great deal of medical professional responsibility involved in the biomodeling and virtual planning process. The aim of this work is to review the key role of radiologists in the usual workflow of patients that require 3D technologies for diagnostic and treatment purposes in ensuring safe practices. Imaging requirements and a short description of the biomodeling process necessary to achieve high quality 3D biomodels is presented. General applications and the main difficulties for implementation of 3D technologies are reviewed.